Epidemiology of Clostridioides Difficile Infection in Portugal: a Retrospective, Observational Study of Hospitalized Patients - Nazareth, C (2022)
Introduction: Clostridioides difficile is the main cause of healthcare-associated diarrhea in Europe and North America. The aim of this study was to characterize the epidemiology and clinical burden of Clostridioides difficile infection among hospitalized patients in Portugal. Material and methods: Retrospective study conducted in six public hospital centers in Portugal. All primary Clostridioides difficile infection episodes and related recurrences occurring in 2017, as well as episodes developing two to eight weeks after the last episode diagnosed in that year, were documented. The National Reference Laboratory (National Institute of Health Dr. Ricardo Jorge) provided national surveillance data on Clostridioides difficile infection. Results: A total of 385 inpatients with at least one primary episode diagnosed in 2017 were included. Most patients were aged over 70 years-old (73.2%). The included patients developed 451 episodes during the observation period. Approximately 44% of primary episodes were community-associated. Most episodes (94.9%) occurred in patients with one or more risk factors, with recent antibiotic exposure being particularly common (86.0%). All-cause in-hospital mortality was 19.5%, being significantly higher in patients aged over 65 years-old versus those aged 18 to 64 years-old (22.4% vs 7.8%, respectively). Over 50 different ribotypes were observed among 206 Clostridioides difficile strains received by the National Reference Laboratory. Conclusion: In Portugal, hospitalized patients with Clostridioides difficile infection are mostly older patients presenting risk factors for the development of this infection, particularly recent antibiotic exposure. Mortality is disproportionately high among the older population. Community-associated Clostridioides difficile infection is common among inpatients with this infection.